Clinical Outcomes of Remdesivir in COVID-19 Patients with Acute Kidney Injury or Chronic Kidney Disease: A Randomized Clinical Trial - Freidoon, Mahboobeh; Alirezaei, Toktam; Khatuni, Mahdi; Assadiasl, Sara (Archives of Men's Health, 2023)
Background: remdesivir is an RNA polymerase inhibitor approved to treat moderate to severe Coronavirus Disease 2019 (COVID-19); however, it has not yet been authenticated to apply to patients with acute kidney injury (AKI) or chronic kidney disease (CKD). Regarding some positive results obtained from previous studies, we aimed to evaluate the efficacy and safety of remdesivir in patients with COVID-19 with severe renal impairment. Methods: In a randomized clinical trial, remdesivir was added to the standard regimen of treating patients with COVID-19 with AKI or CKD. 200 mg remdesivir was given on the first day of admission to 50 patients followed by 100 mg every other day until resolution of the symptoms. Clinical and paraclinical evaluation was performed daily and the findings were compared with the 50 patients on standard treatment regimen. Results: the rates of intensive care unit (ICU) admission (P: 0.02), and mortality (P: 0.007) were significantly reduced in patients who received remdesivir. Moreover, a substantial decrease of aspartate transaminase (AST) (P: 0.004), lactate dehydrogenase (LDH) (P: 0.004), ferritin (P: 0.007), erythrocyte sedimentation rate (ESR) (P<0.0001), alkaline phosphatase (ALP) (P: 0.006) were observed in the patients receiving remdesivir compared to the baseline values which was absent in case of non-remdesivir group. No serious side effects were observed, except for one patient who showed elevated liver enzymes. Conclusion: remdesivir appears to be well tolerated in patients with AKI and CKD. Administration of this drug resulted in reduced mortality and ICU admission as well as clinical and paraclinical improvement in these patients.